Expansion of myelin autoreactive CD8+ T lymphocytes in patients with neuropsychiatric systemic lupus erythematosus. Issue 5 (27th December 2010) - Contin-Bordes, Cécile; Lazaro, Estibaliz; Richez, Christophe; Jacquemin, Clément; Caubet, Olivier; Douchet, Isabelle; Viallard, Jean-François; Moreau, Jean-François; Pellegrin, Jean-Luc; Blanco, Patrick
Abstract : Objectives: Delineation of mechanisms underlying neuropsychiatric systemic lupus erythematosus (NPSLE) and determination of biological markers could guide treatment choice. A study was undertaken to analyse the potential role of activated CD8+ T cells in NPSLE as previously reported in SLE nephritis. Methods: Flow cytometric immunophenotyping of blood lymphocytes was performed in 30 patients with NPSLE and 36 healthy individuals. The antigenic specificity of CD8+ T cells was studied using HLA-A0201 tetramers loaded with several myelin-derived peptides. The intracellular level of interferon γ (IFNγ) produced by activated CD8+ T cells was determined by flow cytometry. Results: A large increase in circulating activated CD8+ T lymphocytes expressing surface HLA-DR was found in patients with NPSLE without antiphospholipid syndrome (APS) (n=18) compared with patients with APS (n=12) or healthy controls (n=36). IFNγ-secreting myelin-specific CD8+ T cells were detected exclusively in the blood of patients with NPSLE without APS but with white matter lesions. Conclusions: These data strongly support the existence of a new immune effector mechanism responsible for CNS involvement in patients with NPSLE and suggest that analysing HLA-DR expression combined with myelin-specific tetramer staining on CD8+ T lymphocytes may be a valuable additional tool for the monitoring of these patients.